2017
DOI: 10.1039/c7py00260b
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of dendron-branched silicone polymers

Abstract: Monofunctional dendritic silicone branches were created from hydro- and alkoxysilanes using the Piers–Rubinsztajn reaction. Monofunctional dendritic silicone branches were added to linear polymers with varied branch frequency, density and backbone molecular weight. Viscosities of the polymers increased with branch frequency to a maximum beyond which the viscosity decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…When linear branches were placed on a low molecular weight linear silicone backbone, little change in resulting viscosity was noted, even at high branch frequencies. By contrast, the grafting of medium, and especially high density, 3D branches on the same backbone led to much higher increases in the viscosity at given frequency (Figure ) . It was also noted that there was a rise in viscosity with increasing branch frequency until a maximum occurred, at which point a globular transition occurred, and the viscosity began to drop with further increases in branch frequency; such a trend has been observed with dendrimers.…”
Section: Piers–rubinsztajn (Pr) Reactionmentioning
confidence: 73%
See 1 more Smart Citation
“…When linear branches were placed on a low molecular weight linear silicone backbone, little change in resulting viscosity was noted, even at high branch frequencies. By contrast, the grafting of medium, and especially high density, 3D branches on the same backbone led to much higher increases in the viscosity at given frequency (Figure ) . It was also noted that there was a rise in viscosity with increasing branch frequency until a maximum occurred, at which point a globular transition occurred, and the viscosity began to drop with further increases in branch frequency; such a trend has been observed with dendrimers.…”
Section: Piers–rubinsztajn (Pr) Reactionmentioning
confidence: 73%
“…showed that, following the PR reaction, Huisgen or azide/alkyne click reactions could be used to create silicone/PEG (or cyclodextrin) surfactants (Figure B), elastomers (Figure C), copolymers or adhesives . The most important orthogonal reaction in silicone systems is platinum‐catalyzed hydrosilylation (see below) …”
Section: Piers–rubinsztajn (Pr) Reactionmentioning
confidence: 99%
“…Monoallyl-terminated silicone dendrons with different degrees of branching were prepared as shown in Figure 2A [14]. First, allyltriethoxysilane underwent the Piers-Rubinsztajn (PR) reaction with either pentamethyldisiloxane ( T(DM) 3 series) or 1,1,1,1,3,5,5,5-heptamethyltrisiloxane ( T(TM 2 ) 3 series) to afford compounds 1 or 2 in good yield.…”
Section: Resultsmentioning
confidence: 99%
“…Mono-vinyl terminated PDMS 7 was prepared according to the literature procedure [14]. The Mn of this polymer was 3165 g mol −1 and dispersity ( Đ M ) was 1.2.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the crosslinkers can be modified, but this approach dramatically decreases the achievable concentrations of high-permittivity filler. [87][88][89][90] By employing the covalent grafting method, immiscibility issues are avoided, of course provided that the reaction mixture was homogeneous initially and the curing did not alter this state. [86] Grafting often requires complex and novel chemistries, since the chemistry of silicones is rather unexplored.…”
Section: Chemically Modified Silicone Elastomersmentioning
confidence: 99%